Multiple roles of NF1 in the melanocyte lineage - Larribere, Lionel; Utikal, Jochen (Pigment cell & melanoma research, 2016)
NF1 is a tumour suppressor gene, germline mutations of which lead to neurofibromatosis type 1 syndrome. Patients develop benign tumours from several types of cells including neural crest-derived cells. NF1 somatic mutations also occur in 15% of sporadic melanoma, a cancer originating from melanocytes. Evidence now suggests the involvement of NF1 mutations in melanoma resistance to targeted therapies. Although NF1 is ubiquitously expressed, genetic links between NF1 and genes involved in melanocyte biology have been described, implying the lineage-specific mechanisms. In this review, we summarize and discuss the latest advances related to the roles of NF1 in melanocyte biology and in cutaneous melanoma.
Gesehen am 08.07.2019